1982
DOI: 10.1136/pgmj.58.679.299
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic jaudice due to toxoplasma hepatitis

Abstract: Summary A case of toxoplasma hepatitis presenting with cholestatic jaundice is described. The diagnosis was based on serological testing and evidence of hepatitis on biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…The presence of liver enlargement and altered biochemical liver function tests indicates hepatic involvement, even in the absence of jaundice. Abnormalities in liver function have been noted by other authors (Tiwari et al 1982, McCabe et al 1987. It is worth noting the absence of abdominal lymph node enlargement.…”
Section: Discussionsupporting
confidence: 58%
“…The presence of liver enlargement and altered biochemical liver function tests indicates hepatic involvement, even in the absence of jaundice. Abnormalities in liver function have been noted by other authors (Tiwari et al 1982, McCabe et al 1987. It is worth noting the absence of abdominal lymph node enlargement.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies (20,23) reported cholestatic jaundice due to T. gondii infection, although the pathogenicity of the jaundice was not revealed. The present results suggested the existence of a novel migration route of T. gondii, from liver to bile and bile to feces, in immunocompromised GKO mice.…”
mentioning
confidence: 99%
“…Hepatitis has been reported in apparently healthy persons during acute infection; these patients present with jaundice, rash, and elevated levels of transaminases and alkaline phosphatase. [492][493][494][495] Histologically, Toxoplasma hepatitis is characterized as a diffuse hepatitis with infiltration of portal tracts and sinusoids by mononuclear cells associated with focal hepatic necrosis, similar to EBV or CMV hepatitis. [492][493][494] Granulomatous hepatitis has also been described.…”
Section: Toxoplasmosismentioning
confidence: 99%
“…[492][493][494][495] Histologically, Toxoplasma hepatitis is characterized as a diffuse hepatitis with infiltration of portal tracts and sinusoids by mononuclear cells associated with focal hepatic necrosis, similar to EBV or CMV hepatitis. [492][493][494] Granulomatous hepatitis has also been described. 495 In some cases, bradyzoite-containing Toxoplasma cysts have been identified in histiocytes and granulomas or within the hepatic parenchyma.…”
Section: Toxoplasmosismentioning
confidence: 99%
See 1 more Smart Citation